2013
DOI: 10.1097/rli.0b013e31828d56a1
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Simultaneously Acquired Diffusion-Weighted Imaging and 2-Deoxy-[18F] fluoro-2-D-glucose Positron Emission Tomography of Pulmonary Lesions in a Dedicated Whole-Body Magnetic Resonance/Positron Emission Tomography System

Abstract: Examinations of pulmonary lesions in a simultaneous whole-body MR/PET system provide diagnostic image quality in both modalities. Although DWI and FDG-PET reflect different tissue properties, there may very well be an association between the measures of both methods most probably because of increased cellularity and glucose metabolism of FDG-avid pulmonary lesions. A voxelwise DWI and FDG-PET correlation might provide a more sophisticated spatial characterization of pulmonary lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
52
2
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(59 citation statements)
references
References 40 publications
4
52
2
1
Order By: Relevance
“…A positive correlation between ADC and 18 F-FDG SUV could seem, at first glance, inconsistent with findings from Schmidt et al, who have reported a negative correlation between SUV max and ADC min (17). However, in accordance with Schmidt et al, the intratumor correlation coefficient is mostly negative for all tumors and becomes more negative as the total tumor volume increases (Supplemental Fig.…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation
“…A positive correlation between ADC and 18 F-FDG SUV could seem, at first glance, inconsistent with findings from Schmidt et al, who have reported a negative correlation between SUV max and ADC min (17). However, in accordance with Schmidt et al, the intratumor correlation coefficient is mostly negative for all tumors and becomes more negative as the total tumor volume increases (Supplemental Fig.…”
Section: Discussioncontrasting
confidence: 53%
“…Recently, Schmidt et al have reported on the correlation of ADC and 18 F-FDG inside of NSCLC tumors using a hybrid PET/MR (17). They applied a Gaussian mixture model (GMM) (18) and theorized that it separated the tumors into distinct and relevant tissue classes.…”
mentioning
confidence: 99%
“…This is of interest, because only the image pattern, but not the underlying information (i.e., tumor property) assessed is similar between the two techniques: DWI visualizes intercellular space narrowing, and thus, cell density (35); whereas 18F-FDG-PET visualizes glucose metabolism, which in turn has been shown to correlate with cell proliferation (36,37). We hypothesize that the reason for our findings is that, at least in the FDG-avid lymphomas included in the present study, there is more glucose consumption in areas of higher cell density, such a correlation between cell density and glucose metabolism has already been reported for malignant lung nodules and pancreatic adenocarcinoma (38,39). In other, very slowly growing lymphomas (e.g., in a certain percentage of MALT lymphomas and SLL/CLL), there may, however, be no such association between cellularity and glucose metabolism.…”
Section: Discussionsupporting
confidence: 51%
“…Preliminary results are available in recent literature on direct comparison between PET/MRI and PET/CT in the staging of lung cancer, mostly non-small-cell lung cancer (NSCLC) [17,[37][38][39][40]; however, many of these studies are limited by small sample size.…”
Section: Lung Cancermentioning
confidence: 99%
“…The performance of PET/MRI has also been studied for the detection of pulmonary nodules [28,40,42 • ]. With use of simultaneous PET and MRI acquisition and a freebreathing radial volumetric interpolated breath-hold examination, the detection of pulmonary nodules was compared with that in PET/CT.…”
Section: Lung Cancermentioning
confidence: 99%